Stability of the emulsion during the injection of anionic and cationic surfactants in the presence of various salts - Hamid Garmsiri; Shahriar Jahani; Yousef Kazemzadeh; Mohammad Sharifi; Masoud Riazi; Reza Azin (Springer Science and Business Media LLC, 2023)
Smart water injection is one of the engineering techniques to enhance oil recovery (EOR) from carbonate and sandstone reservoirs that have been widely used in recent decades. Wettability alteration and IFT are among the essential and influential mechanisms that can be mentioned to achieve EOR. One of the critical issues in the field of EOR is the effect of reservoir ions on the formation and stability of the emulsion. Investigating the role and performance of these ions during EOR processes is of significant importance. These processes are based on smart water injection and natural production. In this research, stability was investigated and formed during the injection of different concentrations of anionic and cationic surfactants, respectively alpha olefin sulfonate (AOS) and cetrimonium bromide (CTAB), into a water–oil emulsion with a volume ratio of 30–70. Considering the droplet diameter distribution and the flow speed of separation by centrifugation, the optimal concentration level has been investigated in both surfactants. Based on the results, the highest stability and emulsion formation occurred in the presence of AOS surfactant. Then different concentrations of CaCl 2 , MgCl 2 , and NaCl salts were added in optimal concentrations of both surfactants. The formation and stability of the emulsion was checked by examining the distribution of the droplet diameter and the separation flow rate. AOS anionic surfactant had the most stability in the presence of MgCl 2 salt, and better performance in stability of the emulsion was obtained. The maximum number of droplet diameters in the optimal concentration for AOS and CTAB surfactant systems is 1010 and 880, respectively, and for binary systems of AOS surfactant and MgCl 2 , CaCl 2 and NaCl salts, it is 2200, 1120 and 1110, respectively. Furthermore, for the CTAB binary system in the presence of MgCl 2 , CaCl 2 , and NaCl salts, it is 1200, 1110, and 1100, respectively. The stability of the emulsion of salts in the presence of both AOS and CTAB surfactants was MgCl2 > CaCl 2 > NaCl.
Keywords: Emulsion; Pulmonary surfactant; Enhanced oil recovery; Chemical engineering; Chemistry; Cationic polymerization; Chromatography; Defoamer; Dispersion (optics); Organic chemistry; Dispersant; Engineering; Physics; Optics; type of access: open access